Hydroxychloroquine Improves Obesity-Associated Insulin Resistance and Hepatic Steatosis by Regulating Lipid Metabolism - Qiao, Xin; Zhou, Zhuo-Chao; Niu, Rui; Su, Yu-Tong; Sun, Yue; Liu, Hong-Lei; Teng, Jia-Lin; Ye, Jun-Na; Shi, Hui; Yang, Cheng-De; Cheng, Xiao-Bing (Frontiers in Pharmacology, 2019)
The burden of obesity and associated cardiometabolic diseases have been considered as an important risk factor for lupus patients. Therefore, the links between obesity and autoimmunity were questioned, and the involvement of obesity in the rise of autoimmune conditions was strongly suggested. Hydroxychloroquine is known as one of the most fascinating synthetic antimalarial drugs, and is presently among the most commonly employed medicines for the clinical treatment of rheumatic diseases. Hydroxychloroquine has been suggested to have beneficial effects on lipids and insulin sensitivity, which may contribute in lowering high cardiovascular risk in SLE patients. However, its mechanism on insulin sensitivity and lipid disorders is far from being completely understood. In the present study, the therapeutic effects of hydroxychloroquine were evaluated under pathological conditions in vivo. Obesity was induced in C57BL/6 mice fed with high-fed diet, or in mice fed with high-fat diet and hydroxychloroquine. In addition, healthy mice that received normal chow diet were also monitored. The present results revealed that hydroxychloroquine reduced weight, hepatic steatosis, glucose and insulin resistance. Furthermore, hydroxychloroquine downregulated the expression of peroxisome proliferator-activated receptor gamma in the liver. According to these present results, lipid metabolism-related genes were downregulated in high-fat mice liver. Hydroxychloroquine shows potential in ameliorating obesity-induced pathology, which acts though PPARγ to facilitate the healthy function of hepatic tissues. This evidence shows that obesity-induced insulin resistance and lipotoxicity can be treated with hydroxychloroquine, which acts though the peroxisome proliferator-activated receptor gamma pathway.